2023
DOI: 10.3389/fcvm.2023.1086603
|View full text |Cite
|
Sign up to set email alerts
|

The role of (pro)renin receptor and its soluble form in cardiovascular diseases

Abstract: The renin-angiotensin system (RAS) is a major classic therapeutic target for cardiovascular diseases. In addition to the circulating RAS, local tissue RAS has been identified in various tissues and plays roles in tissue inflammation and tissue fibrosis. (Pro)renin receptor (PRR) was identified as a new member of RAS in 2002. Studies have demonstrated the effects of PRR and its soluble form in local tissue RAS. Moreover, as an important part of vacuolar H+-ATPase, it also contributes to normal lysosome function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“…In patients with acute decompensated heart failure and chronic heart failure, furin activity is increased due to myocardial stress, which contributes to the elevated levels of BNP to compensate for cardiac function . Consistently, several furin substrates have been shown to contribute to the pathogenesis of heart failure (Figure ), including inflammatory (TNF-α), remodeling/fibrosis (TGF-β1 and MMP2), and hypertrophic (soluble PRR-mediated AT II, BNP, and ET-1) factors, supporting the role of furin in this setting. ,, …”
Section: Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…In patients with acute decompensated heart failure and chronic heart failure, furin activity is increased due to myocardial stress, which contributes to the elevated levels of BNP to compensate for cardiac function . Consistently, several furin substrates have been shown to contribute to the pathogenesis of heart failure (Figure ), including inflammatory (TNF-α), remodeling/fibrosis (TGF-β1 and MMP2), and hypertrophic (soluble PRR-mediated AT II, BNP, and ET-1) factors, supporting the role of furin in this setting. ,, …”
Section: Heart Failurementioning
confidence: 99%
“…Notably, the current evidence suggests that soluble PRR also produces pathobiological functions, including sodium−water retention (via activation of epithelial sodium channel [ENaC]), hypertension (via the local renin−angiotensin−aldosterone system [RAAS]), and heart failure. 53,55 However, there are inconsistencies between preclinical and human data. Several animal studies have demonstrated the association between soluble PRR and hypertension.…”
Section: ■ Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the following studies revealed that the expression of the PRR is not restricted to the kidney. Thus, PRR is present in the heart, testes, brain, placenta, thyroid and adrenal gland, and various cell types of the immune system [ 55 ]. The PRR has the following multifaceted functions: First, binding of renin to the receptor markedly increases its catalytical activity [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because RAS has been elucidated as important in controlling vessel pressure/resistance and salt/water reabsorption of the kidney, evidence has also confirmed the pathogenic role of (P)RR in vascular and kidney-related diseases [ 1 , 3 , 4 ]. Moreover, it has been further suggested that the discovery of (P)RR might provide a plausible rationale for an issue about why a high Ang II activity could be caused by an extreme low expression level of renin in some tissues [ 5 , 6 ]. After two decades of study, (P)RR has been shown to widely express in many types of organs/tissues, e.g., vessel, heart, thyroid, brain, kidney, liver, colon, etc.…”
Section: Introductionmentioning
confidence: 99%